Low temperature route to prepare LaMnO3 - Daundkar, A.; Kale, Sangeeta N.; Gokhale, Suresh P.; Ravi, V (Materials Letters, 2006)
A combination of digestion and further low temperature calcination to crystallize the product is employed to prepare LaMnO3(LM) ceramics. Freshly co-precipitated lanthanum and manganese hydroxides gel is allowed to react at 100 degrees C under refluxing and stirring conditions for 6-12 h. The X-ray amorphous product so formed is heated at 300 degrees C to form crystalline LM powders. This is the lowest temperature so far reported for the formation of LaMnO3. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Chemical synthesis; LaMnO3; Precipitation; transmission electron microscopy; X-ray diffraction